2018
DOI: 10.3389/fpsyg.2018.00724
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Emotion Understanding and Theory of Mind in Children Aged 3 to 8: The Key Role of Language

Abstract: Although a significant body of research has investigated the relationships among children’s emotion understanding (EU), theory of mind (ToM), and language abilities. As far as we know, no study to date has been conducted with a sizeable sample of both preschool and school-age children exploring the direct effect of EU on ToM when the role of language was evaluated as a potential exogenous factor in a single comprehensive model. Participants in the current study were 389 children (age range: 37–97 months, M = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 75 publications
(98 reference statements)
5
37
0
3
Order By: Relevance
“…Children in the first cluster were younger and displayed lower ToM abilities, particularly in the understanding of emotions, consequences, and cognitive mental states. These results are in line with the literature, which has identified a positive and predictive relationship between developmental age and ToM abilities, notably in typically developing children ( Grazzani et al, 2018 ; Conte et al, 2019 ) and in children with IDs (e.g., Charman and Campbell, 2002 ; Baurain and Nader-Grosbois, 2013 ; Nader-Grosbois et al, 2013 ). Children have to display a certain level of cognitive skills to understand mental states ( Cicchetti et al, 1995 ).…”
Section: Discussionsupporting
confidence: 91%
“…Children in the first cluster were younger and displayed lower ToM abilities, particularly in the understanding of emotions, consequences, and cognitive mental states. These results are in line with the literature, which has identified a positive and predictive relationship between developmental age and ToM abilities, notably in typically developing children ( Grazzani et al, 2018 ; Conte et al, 2019 ) and in children with IDs (e.g., Charman and Campbell, 2002 ; Baurain and Nader-Grosbois, 2013 ; Nader-Grosbois et al, 2013 ). Children have to display a certain level of cognitive skills to understand mental states ( Cicchetti et al, 1995 ).…”
Section: Discussionsupporting
confidence: 91%
“…In support of this association, several cross‐sectional studies have found that ToM and emotion understanding are significantly correlated in 3‐ to 5‐year‐olds (Harwood & Farrar, ), 3‐ to 8‐year‐olds (Grazzani, Ornaghi, Conte, Pepe, & Caprin, ), and 4‐ to 6‐year‐olds (Weimer, Sallquist, & Bolnick, ). However, the cross‐sectional nature of these studies does not allow for an understanding of the temporal nature of reported associations.…”
Section: Introductionmentioning
confidence: 81%
“…For instance; studies conducted by Cutting and Dunn, (2006) and Dunn and Brophy (2005) showed that children who were raised in families where mental state and feelings were shared and who participated in such conversations were more successful in assessments on recognition of the mind and emotions. Similarly, Ornaghi, Pepe, Agliati and Grazzani (2018) found that children with high language ability were talented emotional regulation. Milligan, Astington and Dack (2007) conducted a meta-analysis on 104 studies that examined the relationship between false beliefs and language skills in children and found that the false belief performance was associated with language skills.…”
Section: Discussionmentioning
confidence: 84%